SIX SIGMA STATISTIK DENGAN MINITAB DAN EXCEL - Herlawati Herlawati (Paradigma, 2008)
Most companies, nowadays, are applying the six sigma approach to support the quality control of their products. The term six sigma is taken from statistic terms six and sigma. Six means number 6 and sigma means a symbol for a standard deviation. In other words, the standard deviation in use is 6s, meaning that to produce products with 0.002 per one million defect opportunity; the accepted limit of tolerance is 6 times as much as the standard deviation. The existence of noise factor theory which causes shift of mean to the right about 1.5s with 4.4 per one million defect opportunity (DPMO), initiate a number of practitioners to change the term six sigma with 3.4 DPMO, even though it is still controversial. Since most six sigma users are industries with great amount of products, which requires high level of accuracy and speed, thus the use of computer is inevitable. The most common six sigma software programs are Minitab and Excel. Nonetheless, software is only a means. IT is important to understand the essence of statistics so that not only enterprises (industry, trade, and the kind) but also service provider (education, medical, consultant, and etcetera) can apply it for quality control.